Carboxymethylation of Karaya gum: application in gastroretentive drug delivery for sustained release of model drug (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Karaya gum (KG) is one of the least soluble of the gums. It does not dissolve in water to give a clear solution but instead absorbs water rapidly to form viscous colloidal sols. Carboxymethylation of Karaya gum is expected to improve its aqueous solubility and gelling behavior. Another objective of the research is to evaluate the potential of carboxymethylated Karaya gum (CMKG) as drug release modulator (in acidic dissolution medium) when combined with HPMC K15M based polymeric matrices bearing Propranolol HCl. In the present study, KG was carboxymethylated using Williamson Ether synthesis. FTIR spectroscopy confirmed the formation of CMKG. The prepared CMKG was used in conjunction with HPMC K15M as a polymer matrix in the formulation capsule dosage form, using Propranolol HCl as model drug. The filled capsules were then coated with Gelucire 43/01 to convert them into hydrodynamically balanced (HBS) capsule dosage form. Dextrose & fructose were also added to the drug-polymer mix as osmogen to facilitate the drug release. The degree of substitution of CMKG was found to be 0.87. HBS capsule dosage forms remained buoyant on 0.1 HCl for up to 6 hr, the buoyancy was attributed to the Gelucire 43/01 coating around the capsule shell. From the experimentation it was observed that CMKG, when mixed with HPMC K15M at 1:3 ratios, extended the release of model drug from HBS capsule dosage forms in 0.1 HCl. At CMKG: HPMC K15M ratio 2:1, release of Propranolol Hydrochloride from hydrodynamically balanced (HBS) capsules revealed fast drug release in 0.1 HCl. From the observations it is evident that KG is amenable to carboxymethylation to form CMKG. It is also evident that it is advantageous to combine CMKG with HPMC K15M as release modulator to retard the release of Propranolol HCl in acidic dissolution medium.